2023
DOI: 10.1200/jco.22.01873
|View full text |Cite
|
Sign up to set email alerts
|

Mepitel Film for the Prevention of Acute Radiation Dermatitis in Breast Cancer: A Randomized Multicenter Open-Label Phase III Trial

Abstract: PURPOSE Radiation dermatitis (RD) is common in patients undergoing breast radiotherapy. Mepitel film (MF) can reduce RD, but the results from two randomized controlled trials are conflicting. We aimed to conduct a confirmatory randomized controlled trial in patients at risk of RD. METHODS Patients were randomly assigned to receive MF or standard care (2:1 ratio). Patients with large breasts after lumpectomy (bra size ≥ 36 inches or cup size ≥ C) or after mastectomy were eligible. Stratification factors include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 12 publications
0
37
0
4
Order By: Relevance
“… 257 A 2022 trial on Mepitel film similarly demonstrated benefits of Mepitel film in preventing ARD in a population of 376 patients (15.5% vs. 45.6% p < 0.0001). 258 The findings of these recent trials demonstrate a positive trend in the evidence supporting photobiomodulation therapy, topical steroids, and Mepitel film for the prevention of ARD. Overall, among the RCTs identified, 27 demonstrated some significant improvement in RD severity; these latest findings may influence the recommendations made in future guidelines, thus further highlighting a need for regular updates of the literature to reflect ongoing changes in the evidence base.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 257 A 2022 trial on Mepitel film similarly demonstrated benefits of Mepitel film in preventing ARD in a population of 376 patients (15.5% vs. 45.6% p < 0.0001). 258 The findings of these recent trials demonstrate a positive trend in the evidence supporting photobiomodulation therapy, topical steroids, and Mepitel film for the prevention of ARD. Overall, among the RCTs identified, 27 demonstrated some significant improvement in RD severity; these latest findings may influence the recommendations made in future guidelines, thus further highlighting a need for regular updates of the literature to reflect ongoing changes in the evidence base.…”
Section: Discussionmentioning
confidence: 93%
“… 212 In light of this limitation, an updated search has been conducted from September 22nd, 2020 to January 21st, 2023 and revealed 65 new studies, of which 38 are RCTs; a list of the latest RCTs has been provided in Appendix E , along with a summary of RCT characteristics. RCTs were recently published on interventions already identified through the present review, such as Mepitel film, 258 topical corticosteroids, 259 , 260 heparinoid, 261 photobiomodulation, 257 , 262 , 263 aloe vera gel, 264 calendula, 256 and others. Additional RCTs were identified on new interventions not previously explored before September 2020, such as the use of compound Kushen injection, 265 epigallocatechin-3-gallate, 201 , 266 bacterial decolonization, 267 and others.…”
Section: Discussionmentioning
confidence: 99%
“…Mepilex ® , the most popular dressing of choice for the majority of participants, should be used only for moist desquamation. 48 Numerous RCTs showed that a prophylactic application of film dressings significantly reduced moist desquamation and the severity of skin reactions in breast cancer patients, [49][50][51][52][53][54][55] and nasopharyngeal carcinoma. 56 However, the use of barrier films is apparently much better tolerated in breast than in head and neck irradiation as another German RCT in head and neck cancer was terminated prematurely due to patient intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, foam dressings may exert a bolus effect and may require removal during RT, 53 while film dressings proved no relevant impact on skin dose. 49,51,52,58 Even though powder always ranked very low in the efficacy assumption ratings, 7.3% surprisingly still recommend it for topical prevention of RD. The obvious discrepancy between recommendations and efficacy ratings suggests that a paradigm shift has already occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Mepilex ® , der beliebteste Verband bei der Mehrheit der Teilnehmer, sollte nur für die feuchte Desquamation verwendet werden. 48 Zahlreiche RCT zeigten, dass eine prophylaktische Anwendung von Folienverbänden die feuchte Desquamation und den Schweregrad von Hautreaktionen bei Patientinnen mit Brustkrebs [49][50][51][52][53][54][55] und Patienten mit Nasopharynxkarzinomen signifikant reduzierte. 56 Allerdings wird die Verwendung von Folienverbänden bei der Bestrahlung von Brustkrebs offenbar deutlich besser vertragen als bei der Bestrahlung von Kopf-Hals-Tumoren, da eine andere deutsche RCT zu dieser Entität aufgrund von Unverträglichkeiten vorzeitig abgebrochen wurde.…”
Section: Diskussionunclassified